Severe Staffing And Personal Protective Equipment Shortages Faced By Nursing Homes During The COVID-19 Pandemic - McGarry, Brian E; Grabowski, David C; Barnett, Michael L (Health affairs (Millwood, Va.), 2020)
The coronavirus disease 2019 (COVID-19) pandemic continues to devastate US nursing homes. Adequate personal protective equipment (PPE) and staffing levels are critical to protect nursing home residents and staff. Despite the importance of these basic measures, few national data are available concerning the state of nursing homes with respect to these resources. This article presents results from a new national database containing data from 98 percent of US nursing homes. We find that more than one in five nursing homes reports a severe shortage of PPE and any shortage of staff. Rates of both staff and PPE shortages did not meaningfully improve from May to July 2020. Facilities with COVID-19 cases among residents and staff, as well as those serving more Medicaid recipients and those with lower quality scores, were more likely to report shortages. Policies aimed at providing resources to obtain additional direct care staff and PPE for these vulnerable nursing homes, particularly in areas with rising community COVID-19 case rates, are needed to reduce the national COVID-19 death toll.